Cyberreligion: The Spiritual Paradox of Digital Technology - Ridho, Ali; Suja, Aidillah; Taufik, M.; Thibburruhany, Thibburruhany; bin Mawazi, Abd. Rahman; Rahmat, Syahrul; Sidik, Muhammad Alfan; Nisa, Faridhatun; Ali, Muhamad (Ri'ayah: Jurnal Sosial dan Keagamaan, 2023)
The existence of cyberspace has not only changed human views on spirituality, religion, rituals, houses of worship, scriptures, spiritual teachers, beliefs, divinity, and even the view of god itself. Cyberspace opens up the possibility to carry out various religious activities in a new way that is artificial or virtual. Literature review, as part of the scientific approach, focuses on the literature of journal articles, books, monographs that discuss themes based on keywords related to the research conducted. A new cyber vision of God is developing, which is now seen as a projection or incarnation of humanity (mind, intelligence, power) in the form of computer simulations that are considered to have power close to god's power. This is the vision of man as his own god developed by cyberists, a man who is no longer willing to submit to the authority of power beyond his own power - god man.